Pengaruh Amelioran Terhadap Kemasaman dan Ketersediaan P Tanah Ultisol: The Effect of Ameliorants on Acidity and P Availability of Ultisol Soil - Sri Rezeki Makatita; Fakhrur Razie; Ratna Ratna (Acta Solum, 2025)
Ultisol is soil on acidic dry land which has problems such as low organic matter content, soil pH and availability of nutrients, one of which is P-available. Chicken manure and coal ash can function as ameliorant materials so that they can improve fertility in ultisol soil. This research aims to determine the effect of applying ameliorant (chicken manure and coal ash) on the acidity and P availability of ultisol soil. This research used a single factor Completely Randomized Design method with six treatments repeated four times to produce 24 experimental units including PA0 = control, PA1= 100% coal ash (0,25 t ha-1) + 0% chicken manure (0 t ha-1), PA2= 25% chicken manure (0,5 t ha-1) + 75% coal ash (0,75 t ha-1), PA3= 50% chicken manure (1 t ha-1) + 50% coal ash (0,50 t ha-1), PA4= 75% chicken manure (1,5 t ha-1) + 25% coal ash (0,25 t ha-1), PA5= 100% chicken manure (2 t ha-1) + 0% coal ash (0 t ha-1). Providing ameliorants in the form of chicken manure and coal ash can expand soil pH, available P and Ca-dd, can reduce soil Al-dd but cannot expand soil Mg-dd.